Dispersion of rice flour using computational fluid dynamic simulation on possibility of dust explosion - Muhammad Hafeeyi, Zulkafle (2025)
Dust explosions pose a serious risk to public safety in sectors that deal with flammable materials, such as rice flour, and can have catastrophic consequences, including property damage, injuries, and fatalities. The dispersion properties of rice flour at different concentrations (250, 500, 750, and 1000 g/m³) in a 20L spherical explosion chamber are examined in this work using Computational Fluid Dynamics (CFD) models. In order to assess the impact of concentration on dust dispersion and its consequences for explosion hazards, the study focusses on several important parameters, such as static pressure, turbulence kinetic energy (TKE), vector velocity, and particle tracks. The results show that increasing concentrations of dust have a significant impact on the flow dynamics in the chamber. Turbulence kinetic energy peaks at higher concentrations, resulting in chaotic flow dynamics and uneven particle dispersion. Vector velocity patterns at higher concentrations show irregular and overlapping flow paths, with stagnation zones forming where particles accumulate. Particle tracks further demonstrate the effects of increased clustering and non-uniform dispersion, which develop high-density regions prone to ignition. Static pressure gradients become more noticeable at higher concentrations (750 g/m³ and 1000 g/m³). On the other hand, the dust shows finer velocity patterns, less turbulence, and less clustering at lower concentrations (250 g/m³ and 500 g/m³). There is less chance of an explosion or ignition under these circumstances. The study emphasises how crucial it is to maintain ideal dust concentration and flow conditions in order to successfully reduce the risk of explosions. The research helps to create safer industrial processes and better explosion prevention techniques by offering a thorough analytical approach to analyse dust dispersion behaviour.